Modification of Sago Starch-Based Bioplastic Using Citric Acid with Variation Plasticizers Glycerol and Sorbitol: Properties and Biodegradability Studies - ojsadmin; Trisuciati Syahwardini; Cindy Oktaviani; Vivi Novriyani; Said Zul Amraini; Bahruddin (Jurusan Teknik Kimia, Fakultas Teknik, UNRI, 2020)
Bioplastic or biodegradable plastic is one of alternative replacement to conventional plastic that has the potential to harmful to the environment. One of the raw material that has the potential to be made into bioplastic is sago starch because it has ability to degraded. The general purpose of this research is to determine the characteristics of sago-based bioplastic by modified the citric acid, microcrystalline cellulose filler, plasticizer sorbitol and glycerol. The synthesis method is casting of starch, water, filler Micro Cristalline Cellulose (MCC) with varying plasticizer sorbitol and glycerol with composition of filler is (15-25 % w/w), composition of plasticizer (25– 35 % w/w), and composition citric acid (3-9 % w/w). The results showed that the treatment with the addition of MCC fillers, plasticizers, and citric acid are contributed to the mechanical properties produced. In the best process conditions (20% w/w MCC filler, plasticizer sorbitol 30% w/w with citric acid 0.95% w/w) give result Tensile strength 15.84 MPa, Elongation 9.32%, Young's Modulus 171.2 MPa, Biodegradation 51.65%, and wavelength absorption 1722.51 cm-1